Removal of Methylene Blue from Wastewater by Waste Roots from the Arsenic-Hyperaccumulator Pteris vittata: Fixed Bed Adsorption Kinetics - Mazzeo, Leone; Marzi, Davide; Bavasso, Irene; Piemonte, Vincenzo; Di Palma, Luca (Materials, 2023)
Phytoremediation of arsenic-contaminated water was successfully conducted by means of the perennial fern Pteris vittate, which is an arsenic-hyperaccumulator plant able to grow in hydroponic cultures. In order to avoid the costs linked to the disposal of As-contaminated biomass, in this work, Pteris vittata waste roots were tested as a low-cost bio-adsorbent for the removal of methylene blue (MB) from water in a fixed-bed adsorption configuration. As a matter of fact, methylene blue can negatively impact the growth and health of algae and plants by blocking light from reaching them in water, which can alter their normal biological processes. Previous works have already shown the potentiality of such material toward the uptake of methylene blue; however, all the studies conducted were just focused on batch-mode experiments. In this work, column runs were carried out at 20 °C, evaluating the bed void fraction for each test and hence estimating the apparent density of the material (300 g/L). The breakthrough curves collected were fitted by means of a mathematical model based on the linear driving force (LDF) approximation to obtain information on the mass transfer mechanism occurring in the system. A relation for the product between the LDF mass transfer coefficient and the solid specific surface (kLDFas) with respect to the Reynolds (Re) dimensionless number was obtained (kLDFas=0.45Re). The range of validity of such expression was Re<0.025. Its applicability was deeply discussed: in such conditions, the technology is ready to be tested at larger scales.